PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PT. PANCA TUNAS HARAPAN KOTA SORONG - Lestari Aprilia; Susetyowati Sofia; Agilistya Rahayu (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to see (1) the effect of reward on the performance of employee at PT. Panca Tunas Harapan Sorong City. (2) The effect of punishment on the performance of employee at PT. Panca Tunas Harapan Sorong City. This research uses descriptive and correlation methods using a quantitative approach. The population in this study are all employees who work at PT. Panca Tunas Harapan Sorong City totaling 60 people. The sampling technique used purposive sampling with a sample size of 52 people. Of the study are interview, observation, documentation, and questionnaires. The data analysis technique used is multiple linear regression analysis. The results showed that : (1) Reward has a positive effect on employee performance at PT. Panca Tunas Harapan Sorong City. This is evindenced by the t count value of 4.739 > t table of 2.00958 with a significant value of 0.000 < from the significance level of 0.05 and the regression coefficient having a positive value of 0.112. (2) Punishment has a positive effect on employee performance at PT. Panca Tunas Harapan Sorong City. This is evidenced by the t count value of 8.907 > t table of 2.00958 with a significant value of 0.000 < from the significance level of 0.05 and the regression coefficient having a postive value of 0.650